(untitled) (Халықаралық қатынастар және халықаралық құқық сериясы, 2025)
The article examines the transformation of the discourse on illegal immigration as one of the central and controversial topics of American politics (2009-2021). The theoretical framework of the research is based on Ole Wæver’s securitisation theory. The methodology is presented by a mixed-method approach that combines content and sentiment analysis. The main purpose of the quantitative method is to count the number of keywords defined by the authors in the official speeches of politicians. The objective of the qualitative method is to evaluate all the matches from the sample on a scale of "rigidity" in the contextual framework of political statements. The authors conclude that there is a considerable degree of difference in the rhetoric of Obama and Trump, with statements by the former being categorised as neutral or negative, and those by the latter being predominantly positive or neutral. The article contributes to closing the gap in existing research by providing a comprehensive analysis of the presidential discourse related to illegal immigration to the United States. In the final part of the article, the authors believe that the tendency to build a narrative about illegal immigration through the prism of securitisation will continue to be a characteristic feature of the new Trump, elected in 2024. Key words: securitisation, Barack Obama, Donald Trump, official discourse, illegal migration